2019
DOI: 10.1038/s41598-019-45114-1
|View full text |Cite|
|
Sign up to set email alerts
|

Liver sinusoidal endothelial cells (LSECs) modifications in patients with chronic hepatitis C

Abstract: The sinusoidal endothelial cells present in the liver (LSECs) are tipically characterized by the presence of pores (fenestrae). During some pathological conditions LSECs undergo “capillarization”, a process characterized by loss of fenestrations and acquisition of a vascular phenotype. In chronic liver disease capillarization has been reported to precede the development of fibrosis. LSECs modification in the setting of HCV infection is currently poorly investigated. Considering that HCV accounts for important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 44 publications
4
28
1
Order By: Relevance
“…Similarly, CD34 staining, endothelial cell markers clearly show the CD34positive capillaries and sinusoids of liver tissue in the control rats, but not for DEN induced rats, implying that there are abnormalities of liver sinusoidal endothelial cells (LSECs). 23 Because hepatic sinusoid acts as a selective barrier between the blood and liver parenchyma, alteration of sinusoidal functions and morphologies might lead to leakage of hepatic capillaries and sinusoids, thereby causing Fe-TA NPs to penetrate liver parenchyma. In addition to abnormalities of hepatic sinusoids, capable of taking up of Fe-TA NPs by hepatocytes is also critical implications for their accumulation and MRI enhancement efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, CD34 staining, endothelial cell markers clearly show the CD34positive capillaries and sinusoids of liver tissue in the control rats, but not for DEN induced rats, implying that there are abnormalities of liver sinusoidal endothelial cells (LSECs). 23 Because hepatic sinusoid acts as a selective barrier between the blood and liver parenchyma, alteration of sinusoidal functions and morphologies might lead to leakage of hepatic capillaries and sinusoids, thereby causing Fe-TA NPs to penetrate liver parenchyma. In addition to abnormalities of hepatic sinusoids, capable of taking up of Fe-TA NPs by hepatocytes is also critical implications for their accumulation and MRI enhancement efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Following production of substantial basement membrane, the phenotypic alterations in LSEC become virtually irreversible. Capillarisation is analogous with endothelial dysfunction, in which LSEC can no longer maintain HSC quiescence in response to shear stress signals ( Deleve et al, 2008 ; Xie et al, 2012 ), and together these processes precede fibrosis ( Horn et al, 1987 ; Fraser et al, 1991 ; Pasarín et al, 2012 ; Baiocchini et al, 2019 ). A recent study, however, showed that LSEC dysfunction and loss of fenestrations following chronic metabolic stress do not always go hand in hand ( Kus et al, 2019 ).…”
Section: Lsec Pathophysiologymentioning
confidence: 99%
“…It is well-documented that fenestrations are altered in pathophysiological conditions ( Horn et al, 1987 ; Clark et al, 1988 ; Fraser et al, 1991 ; Xu et al, 2003 ; Baiocchini et al, 2019 ). Fenestrations also decrease with age ( Ito et al, 2007 ), a process dependent on p53 and p19 ARF - dependent signalling ( Koudelkova et al, 2015 ) which is associated with pseudocapillarisation, sinusoidal dysfunction, loss of vasodilatory capacity, and increased hepatic vascular resistance ( Dg et al, 2007 ; Jamieson et al, 2007 ; Maeso-Diaz et al, 2018 ).…”
Section: Lsec Pathophysiologymentioning
confidence: 99%
“…Samples were then dehydrated in graded ethanol and embedded in Epon resin, as previously described [14,15]. Ultrathin sections were stained with 2% uranyl acetate and observed under a transmission electron microscope JEOL JEM 2100 Plus (Japan Electron Optics Laboratory Co. Ltd. Tokyo, Japan).…”
Section: Light and Transmission Electron Microscopymentioning
confidence: 99%